MEMPERKUAT KEPUTUSAN PEMBELIAN JASA URBANCUT BARBERSHOP MELALUI MEDIASI CITRA TOKO - Alala, Legazea Syifa; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2017)
This study aims to strengthen purchase decision Urbancut barbershop services. Starting from sales decline problem of Urbancut services and created a research question: "How to strengthen the purchasing decisions Urbancut services?". Literature review conducted produce a research model to strengthen the purchase decision through the mediation of store image with independent variable social media marketing and haircut quality.            This research using purposive sampling method with sample of 75 respondents which are customers and followers of Urbancut social media accounts. Using SPSS 23 analyzes performed included: validity and reliability, the classic assumption test, multiple regression analysis, hypothesis testing through t and F test, as well as the coefficient of determination (R2).            The results showed 63% purchase decision variable is explained by the store image as the mediation of social media marketing and haircut quality affects 44.6%. As well as the direct influence haircut quality of 38%. Overall variables used in this research have positive impacts to strengthen Urbancut services purchasing decisions.